Menuju Perlindungan Sinergis: Diagnosis Kesenjangan Tata Kelola Kolaboratif bagi Pekerja Migran Indonesia di Jawa Tengah - Supriyanto, Hery; Hartawan, Wisnu (Journal of Politics and Policy, 2025)
This study explores the gaps and enabling factors in implementing collaborative governance to protect Indonesian Migrant Workers (PMI) at the regional level, using Central Java as a case study. Despite existing policies, protection remains government-dominated, with limited non-governmental involvement. Preventive efforts are lacking because responses tend to be reactive. Through qualitative document analysis, this study examines four dimensions: initial conditions, institutional design, leadership, and collaboration processes. The findings indicate ineffective collaboration due to weak stakeholder engagement. Strengthening partnerships between government and non-governmental actors is essential to enhance migrant worker protection and contribute to regional poverty reduction efforts